Correlation of antibiotics prescribing appropriateness based on the pharmaceutical care network europe (PCNE) method and clinical response in Community-Acquired Pneumonia - Cut Fatia Ulfa; Woro Supadmi; Dyah Aryani Perwitasari; Endang Yuniarti (Universitas Ahmad Dahlan, 2022)
The use of antibiotics as the main standard of pneumonia treatment is usually prescribed in high quantities. Inappropriate selection of antibiotics can lead to bacterial resistance, treatment failure, and the emergence of DRPs (Drug-Related Problems). This study aims to determine the suitability of antibiotic prescribing using the PCNE method and to determine the correlation between the suitability of antibiotic prescribing and clinical response. This study was analyzed using a retrospective analytic cohort study method with data collection of adult Community-Acquired Pneumonia patients medical record, who were hospitalized in private hospital in Yogyakarta from January to December 2019. In addition, this study also assessed antibiotic prescribing according to the PCNE V8.02 method toward patients’ clinical response (the number of leukocyte, temperature, and respiratory rate) after take the antibiotics. The correlation according to antibiotic prescribing analyzed according to chi-square method. The results showed that a total of 52 antibiotic regimens obtained in the evaluation of antibiotic prescribing according to the PCNE method were 21.5% suitable and 78.8% not suitable. Thus, the results of the correlation test for the accuracy of antibiotic prescribing and clinical response to the number of leukocytes showed a significant relationship (p<0.05). However in this study, none significant correlation was found in antibiotic prescription and clinical response in terms of temperature and respiratory rate (p<0.05).